Experience of Endovascular Treatment of Pulmonary Artery Atresia - Elnur Imanov; Igor O. Ditkivskyy; Oleksandr I. Plyska; Oleksandra A. Mazur; Artemiia O. Sloboda (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To analyze the results of the use of endovascular treatments for pulmonary artery atresia (PAA).Materials and methods. Treatment of this heart defect at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine with application of endovascular methods began in 2006. Since then, 138 patients were operated, 57 of them female (41.3%) and 81 (58.6%) were male. Endovascular methods were used in 23 patients, and 115 patients underwent open-heart surgery. The mean length of hospital stay was 25±16.3 days.Of 115 patients who underwent open-heart surgery, 62 (54%) were male and 53 (46%) were female. On the day of surgery, the mean age of these patients was 607.8±1023.7 days, mean weight was 8.8±8.1 kg. The average length of hospital stay was 26±18.6 (maximum 215, minimum 5). Of 23 patients who underwent endovascular surgery, 18 (77%) were male and 5 (23%) were female. The mean age on the day of surgery was 220.5±650.2 days, mean weight was 5.0±4.4 kg. The mean length of hospital stay was 22±5.7 days (maximum 34, minimum 4).In the treatment of PAA, a stepwise procedure is used, correcting part of the defect at each stage and thereby reducing the traumaticity of the operation. In our case, correction of the defect was performed on the open heart and using endovascular methods of treatment. After endovascular interventions, no fatal effects were observed. Open-heart surgery was performed in case if endovascular interventions could not be performed. The condition of such patients was usually more severe. It should also be noted that the open-heart surgery itself is a serious trauma to the body. Due to the above, postoperative period in this group of patients more often proceeded with complications. Due to more severe preoperative condition of the patients and surgical trauma, in some cases of open-heart interventions, some patients did not recover after surgery. As a result, the total mortality in the group of patients who underwent open-heart surgery was 13.0%. In addition, in 7 cases, such surgery was supplemented by the Rashkind procedure. In case of recurrent surgery after 6 months, stenting of patent ductus arteriosus was performed. Repeated surgical interventions were accompanied by the improvement of the condition and the patients were discharged from the clinic in satisfactory condition.Conclusions. PAA is one of the most complex congenital pathologies of the heart and main vessels, and therefore preservation of such a newborn depends on the preservation of patent ductus arteriosus. Endovascular surgery for PAA is the operation of choice that allows to prepare the patient for the next stage of treatment, including open-heart surgery. Endovascular interventions in PAA are minimally invasive, which increases the chances of patients with complicated anatomy to survive despite their serious condition on admission to the hospital.